A Three‐Step Synthesis of the Guaianolide Ring System. Issue 15 (11th April 2014) - Hullaert, Jan; Laplace, Duchan R.; Winne, Johan M.
Abstract: By using a gallium(III) triflate catalyzed intramolecular (4+3) cycloaddition, a few functionalized furan‐derived tricycles that share the common guaianolide sesquiterpene ring system were prepared in a stereoselective manner in only three steps from commercially available starting materials. A discussion of the formation of alternative products is included, with possible substrate requirements to achieve the key cycloaddition step in an efficient way. Abstract : The guaianolide ring system, a naturally abundant tricyclic sesquiterpenoid scaffold, is assembled in just three straightforward synthetic operations by using a highly diastereoselective intramolecular (4+3) cycloaddition reaction of a catalytically generated furfuryl cation intermediate.